The Notary's Responsibility for Violations of the Notary's Ethics in Mimika District - Rezalita, Ajeng Berenda (International Journal of Law Society Services, 2024)
A notary is a public official who has the authority to make authentic deeds and other authorities as referred to in Law of the Republic of Indonesia Number 2 of 2014 concerning the Position of Notary Public. There are authorities, obligations and prohibitions that must be obeyed, which will give rise to responsibilities that coincide with the ethical provisions in carrying out his official duties, this research aims to determine and analyze the responsibility of Notaries regarding violations of the Notary's code of ethics as well as the handling of Notaries who are suspected of violating the Notary's code of ethics. The problem formulation in this research was analyzed using the Theory of Responsibility and the Theory of Legal Certainty. This research uses empirical legal research using the approach used in this research is an interdisciplinary method. The results of this research conclude that the author has interviewed 2 (two) notaries and 7 (seven) notary service users in Mimika Regency. So the first result was obtained, there were several violations of the code of ethics, namely the absence of a Notary in his office during the process of making the deed, determining the honorarium which was not in accordance with what had been determined, inappropriate use of social media for an official who was authorized by law and are bound by the oath of office. Second, a notary who is proven to have violated the Notary Code of Ethics can be given ethical sanctions from the Head of the Organization in the form of a warning and as a consequence the responsibility of the official concerned is to cooperatively accept it and not repeat similar violations so that it does not reach the Regional Supervisory Council or the Regional or even Central Government.Keywords: Code; Ethics; Responsibility; Violation.